A method for estimating the polymer gel granule volume by an optical technique - Tokmachev, M.G. (Kompʹûternaâ optika, 2023)
The paper proposes an algorithm for processing a photo of a granule in order to determine its volume. Factors that influence the result of automatic data processing in the optical micrometry method are investigated. It is shown that by estimating the outline of an ellipse-shaped granule, the algorithm determines its volume with a relative error of 0.4 %, which corresponds to an error in determining the granule diameter of 1 pixel.